Dynamic analysis of wind turbines including nacelle–tower–foundation interaction for condition of incomplete structural parameters. (March 2017) - Wang, Shuangyuan; Huang, Yixiang; Li, Lin; Liu, Chengliang; Zhang, Daqing
Considering the complexity structure of wind turbines, it is difficult to establish an accurate model for wind turbines. This article proposed an improved model based on the vibration signal analysis to investigate the onshore wind turbine dynamic behavior. The model is formulated using the Euler–Lagrangian approach in which the dynamic interaction effects between the nacelle and the tower and the effects between the tower and the foundation are considered. The nacelle is assumed as a mass with 2 degrees of freedom at the top of a flexible tower. And the tower is considered as a beam with elastic end support. The foundation stiffness can influence the dynamic response of wind turbines due to the soft soils surrounding the tower base. A rotational spring and a lateral spring derived from the foundation are used to reflect the interaction between the tower and the foundation. Finally, a comparison with existing National Renewable Energy Laboratory 5-MW baseline wind turbine model is performed. And a field experiment has been implemented to validate the model. The vibration signal of the nacelle and the tower is analyzed to determine the model parameters. Results show that the proposed model is accurate and practical for dynamic property analysis of wind turbine.